Challenges to improving patient outcome following massive transfusion in severe trauma. Issue 4 (2nd April 2020) - Maegele, Marc
ABSTRACT: Introduction : Uncontrolled hemorrhage with trauma-induced coagulopathy (TIC) still represents the most common cause of preventable death after trauma. Timely diagnosis and treatment including bleeding control and hemostatic resuscitation to correct TIC are important, as death from exsanguination occurs rapidly. Recognizing who requires an early massive transfusion together with the initiation of corresponding massive transfusion protocols (MTPs) is key to outcome. Areas covered : This expert review summarizes the current state of MT including the activation and termination of MTPs, complications of MT, and strategies for refinement in the administration of blood products in order to avoid harmful over-transfusion. Expert opinion : MTPs should be initiated and continued until normal physiologic parameters are reached and definitive control of bleeding is achieved. Hospitals should develop their own MTPs, guided by evidence, and according to local infrastructure, logistics, needs and patient populations. Massive transfusion, defined as > 10 units of packed red blood cell concentrates (pRBCs) within the first 24 hours of hospital admission, can be life-saving, but is not without complications. MTPs are currently being refined through targeted and early goal-directed approaches which include functional coagulation testing assays to better guide the administration of blood products and hemostatic agents once the patient is stabilized.